The Treatment of Adult Osteochondritis Dissecans with Autologous Cartilage Implantation: A Systematic Review - Sacolick, Davidson A.; Kirven, James C.; Abouljoud, Moneer M.; Everhart, Joshua S.; Flanigan, David C. (The Journal of Knee Surgery, 2019)
We sought to evaluate the effectiveness of autologous chondrocyte implantation (ACI) for the treatment of adult osteochondritis dissecans (OCD) lesions according to patient-reported outcomes, complication rates, and failure rates. A search of MEDLINE, Scopus, and Cochrane Library was performed to identify clinical studies (levels I–IV) reporting outcomes after ACI treatment for OCD in adult knees. Our inclusion criteria included the following: (1) published between January 2000 and April 2017, (2) stable and unstable OCD lesions of the knee, (3) use of ACI in at least one group, (4) subjects ≥18 years old or skeletally mature, (5) inclusion of at least one patient-reported clinical outcome measure, and (6) written in English. A total of nine studies (179 patients), mean age of 27.6 years (range: 18–49 years), were included. There were 227 OCD lesions with an average size of 4.1 cm2 (range: 1.2–9.4 cm2). The average follow-up was 61.3 months (range: 6.5–120 months). In general, there was significant improvement in symptoms, but better results occurred among active male patients with smaller lesions as well as younger patients. Statistically significant improvement in patient-reported outcomes was reported in all studies. There were 23 complications reported (15.6%), including 12 failures (8.2%). Significant improvement in clinical outcome measures demonstrates clinical efficacy of autologous cartilage therapies for the treatment of OCD in adult patients. Better outcomes are often observed with males, active patients, smaller lesion sizes, and younger age at the time of surgery.
Keywords: autologous chondrocyte implantation; osteochondritis dissecans; microfracture; matrix-induced autologous chondrocyte implantation